Characterization of the immune response against Testudinid herpesvirus 3. (International Journal of Health, Animal Science and Food Safety, 2016)
Numerous infectious diseases have been documented in reptiles, however minimal information isavailable concerning their immunological response. One of the most diffuse and lethal reptile pathogenis Testudinid herpesvirus 3 (TeHV3), a Alphaherpesvirinae. All species of tortoises (Testudinide) areconsidered susceptible to TeHV3, however the virus is over represented in the genus Testudo, whichincludes, among others, T. graeca, T. hermanni, T. marginata, and T. horsfieldii, that are popular pets inEurope. Incidence of TeHV3-associated disease is highest right after hibernation (Origgi, 2012).The aim of this work is to partially characterize the immunological response of T. graeca against TeHV3.A bacteriophage library composed of about 5.000 clones containing genomic DNA fragments of TeHV3was produced. Bacteriophages were amplified in a specific strain of E. coli and were screened withTeHV3-seropositive sera from T. graeca. Phagemids were excised from the positive bacteriophages,sequenced, and compare with the TeHV3 genome to identify the encoding genes. Six differentstructural and non-structural proteins have identified as immune relevant. Vero cells where transfectedwith phagemids of the positive clones, to confirm previous results. TeHV3’s proteins expression wasassessed by F.A.C.S using T. graeca seropositive sera. Of all the six selected clones, only that expressingthe partial sequence of the glycoprotein B (gB) showed a positive signal in the F.A.C.S. analysis. Thisresult is consistent with the well-known immunogenicity of gB of other herpesviruses including thoseinfecting humans and with the highly conserved role that gB plays in host-pathogen interaction acrossspecies and evolution (Beals et al., 2016).
Keywords: Testudinid herpesvirus; TeHV3; Reptile Immunology; Testudo